Meningkatkan hasil belajar siswa tentang sistem peredaran darah dengan pembelajaran kooperatif tipe CIRC dan TGT - Wahyuni, Andina; Atmaja, Gilang Tri; Khasanah, Khayatun; Maulida, Novi Apriani; Zaini, Muhammad; Putra, Aminuddin Prahatama; Fajeriadi, Hery; Hartati, Deffi; Khatimah, Husnul (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Cooperative learning offers a promising alternative for improving student understanding. CIRC method (Cooperative Integrated Reading and Composition) and TGT (Teams Games Tournaments) are two types of cooperative learning designed to increase student engagement through collaboration and active interaction. This research aims to explore the application of the CIRC and TGT methods in teaching the human circulatory system, as well as analyzing their impact on the learning outcomes of class XI science students. This research consisted of 2 cycles with 5 meetings. The first cycle was held in 3 meetings, while the second cycle was held in 2 meetings. Cycle 2 is carried out based on the results of reflection from cycle 1. There are several experts who put forward action research models with different charts, but in general there are four stages that are commonly followed, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. Analysis of research data which is classified as quantitative data in the form of learning completeness results obtained from pre-test and post-test results is carried out descriptively, namely by calculating classical completeness and individual completeness. Cooperative learning types TGT and on the concept of the human circulatory system at SMAN Banjarmasin are effective in improving student learning outcomes. This can be seen from the lower percentage increase in classical completion in cycle 2 from cycle 1. However, TGT showed a more significant increase in classical completion than CIRC in cycle 2.Pembelajaran kooperatif menawarkan alternatif yang menjanjikan untuk meningkatkan pemahaman siswa. Metode CIRC (Cooperative Integrated Reading and Composition) dan TGT (Teams Games Tournaments) merupakan dua tipe pembelajaran kooperatif yang dirancang untuk meningkatkan keterlibatan siswa melalui kolaborasi dan interaksi aktif. Penelitian ini bertujuan untuk mengeksplorasi penerapan metode CIRC dan TGT dalam pengajaran sistem peredaran darah manusia, serta menganalisis dampaknya terhadap hasil belajar siswa kelas XI IPA. Penelitian ini terdiri dari 2 siklus dengan 5 kali pertemuan. Siklus pertama dilaksanakan 3 kali pertemuan, sedangkan siklus kedua dilaksanakan 2 kali pertemuan. Siklus 2 dilaksanakan berdasarkan hasil refleksi dari siklus 1. Beberapa ahli menyusun model penelitian tindakan dengan berbagai bagan, namun umumnya terdapat empat tahapan: (1) perencanaan, (2) pelaksanaan, (3) pengamatan, dan (4) refleksi. Analisis data hasil penelitian yang tergolong data kuantitatif berupa hasil ketuntasan belajar yang diperoleh dari hasil pretes dan postes dilakukan secara deskriptif, yakni dengan menghitung ketuntasan klasikal dan ketuntasan individual. Pembelajaran kooperatif tipe TGT dan CIRC pada konsep sistem peredaran darah manusia di SMAN Banjarmasin efektif dalam meningkatkan hasil belajar siswa. Hal ini terlihat dari persentase kenaikan ketuntusan klasikal pada siklus 2 dari siklus 1 yang lebih rendah. Namun, TGT menunjukkan peningkatan ketuntusan klasikal yang lebih signifikan dibandingkan CIRC pada siklus 2.